Anatomical structures in the rabbit carpal tunnel - Yavas, Firuze Turker (Slovenian veterinary research, 2024)
In this study, it was aimed to reveal the morphological and morphometric changes of anatomical structures passing through the carpal tunnel, which is an entrapment neuropathy location for the median nerve. It was also aimed to evaluate the potential of rabbits as an animal model for carpal tunnel research. New Zealand rabbit cadavers were enrolled, and their wrists were investigated using the histological method in this study. ImageJ was used to measure histological sections stained with hemoxylin-eosin. The carpal tunnel was examined at three levels: entrance, inside, and exit. Flexor retinaculum comprises two layers, encircling the carpal tunnel from the palmar side. The deep and superficial digital flexor tendons, and radial carpal flexor tendon were observed within the carpal tunnel but not the flexor pollicis longus tendon. The median and ulnar vascular nerve bundles reside between two layers of flexor retinaculum in the carpal tunnel. The areas of these anatomical structures were measured from images at three levels. Since the flexor retinaculum was located at the entrance and inside, the carpal tunnel area was measured at both levels. The narrowing in the area from the carpal tunnel entrance to the inside of the carpal tunnel in rabbits and the decrease in connective tissue bring the anatomical structures here closer together. This clearly demonstrates that the carpal tunnel is an entrapment neuropathy area, particularly for the median nerve. Upon comparing rabbit and dog carpal tunnel anatomy, it has been shown that rabbits exhibit a greater resemblance to humans, particularly with regard to the flexor retinaculum. This study emphasizes the importance of using the rabbit model to gain insights into carpal tunnel syndrome. It demonstrates similarities between rabbit and human anatomy, underscoring the value of this animal model for future research.
Keywords: carpal canal; flektorni retinaculum; flexor retinaculum; histologija; histology; karpalni kanal; median nerve; mediani živec; morfometrija; morphometry; ulnar nerve; ulnarni živec